Legalising marijuana for medical purposes: is it as bad as society thinks? - Mior Ahmad Shahar, Mior Muhammad Darwisy; Ismail, Nurisfahalin Najihah; Mohamad Fadzli, Nur Alia Nafisa; Mohd Shahrun Nawal, Rayyan Ahmad; Mohd Shakir, Syatrah Hanaany; Saleh, Muhammad Ridhwan (Asian Scholars Network, 2025)
Marijuana has been used extensively throughout the world for a multitude of purposes. Its history can be traced from Shen Nung, a Chinese Emperor, way back in 2727 B.C. Marijuana also was extensively known to the ancient Greeks and Romans, with usage extended throughout the Islamic empire in the Middle East and North Africa. Marijuana first appeared in the Western Hemisphere in 1545, when Spaniards brought it to Chile to use as fibre. Many plantations in North America grew hemp, or Cannabis, for use in paper, clothing, and rope manufacturing. With this, legislation comes into play as a form of societal order to mitigate the adverse effects that come along with Marijuana. Among the earliest legislation to regulate the application of Marijuana can be found in India where it introduces tax for Marijuana and the law on banning of marijuana only comes later in British India and Singapore. Since then, legislation regarding Marijuana has evolved to a point where it encourages discourse regarding the validity of said law. The inquiries still stand on why marijuana is legal and illegal in some jurisdictions, what the medicinal properties of marijuana are if it does have benefits, and whether it outweighs the disadvantages. This study will comparatively examine the existing laws and regulations as well as their implications from various jurisdictions on the usage of marijuana for medical and recreational purposes. Besides that, this study will identify the perception of law students and medical practitioners on the legalisation of marijuana especially for medical purposes by using a self-administered questionnaire distributed to 115 respondents. Data analysis was performed using Google Forms to obtain all the necessary data and figures. The results of this study can be used by policymakers to consider legalising marijuana with a proposed effective legal framework.